Conserving Industrial Architecture in Asia: Problems and Prospects - Johannes Widodo (SARGA Jurnal Arsitektur UNTAG Semarang, 2019)
The debate on industrial heritage in Asia is directly related to the history ofindustrialization and modernization process that happened during the colonial period in many Asian countries. Rapid economic and urban development in Asian countries have put a lot of pressure to the efforts to conserve, even the significant industrial heritage, due to ignorance, economic greed, speculative development, etc. The article is attempted to look into the issues related to the reasons for conservation and the problems for the conservation efforts using some cases in Singapore and Indonesia to pin‐point the direction for the theoretical and practical discourse in the conservation of modern industrial Architecture in Asia.